2010
DOI: 10.1111/j.1745-4530.2009.00505.x
|View full text |Cite
|
Sign up to set email alerts
|

ENERGY AND EXERGY ANALYSES ON DRYING OF OLIVE LEAVES (OLEA EUROPAEA L.) IN TRAY DRIER

Abstract: Recently, olive leaves have a high potential for industrial exploitation in the food industry. The main process in olive leaf treatment is drying. Because drying is an energy‐intensive process, analyzing and improving the drying systems is important. In this study, olive leaves were dried in a tray drier and the performance of the drying process was evaluated using energy and exergy analyses methods. The effects of the drying air temperature and the velocity on the performance of the drying process were discus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
10
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(20 citation statements)
references
References 23 publications
9
10
0
1
Order By: Relevance
“…The exergy efficiency for microwave drying of kiwi slices for the conditions studied was in the range of 11.35-24.68 % (Table 3) while the energy efficiency was higher for the same conditions (P ≤ 0.05). These results were similar with the results in the literature (Akpinar et al 2006;Corzo et al 2008;Erbay and Icier 2009;Bozkurt 2009). The energy efficiency values mainly showed the heat losses to the environment and energy losses caused by irreversibility.…”
Section: Exergy Analysessupporting
confidence: 93%
“…The exergy efficiency for microwave drying of kiwi slices for the conditions studied was in the range of 11.35-24.68 % (Table 3) while the energy efficiency was higher for the same conditions (P ≤ 0.05). These results were similar with the results in the literature (Akpinar et al 2006;Corzo et al 2008;Erbay and Icier 2009;Bozkurt 2009). The energy efficiency values mainly showed the heat losses to the environment and energy losses caused by irreversibility.…”
Section: Exergy Analysessupporting
confidence: 93%
“…The obtained results were good consistent with data reported by Corzo et al (2008) for Coroba slice drying, Aviara et al (2014) for cassava starch drying, lesser time required for drying of product with increase in drying and Erbay & Icier (2011) for olive leaves drying. The variation in exergy efficiency with respect to temperature is inversely to the Figure 4 Plot of lnMR against drying time at various drying air temperatures Figure 5 Effective moisture diffusivity as a function of drying air temperatures Figure 6 Plot of LnDeff against reciprocal of temperature (1/T) for estimation of activation energy energy consumption.…”
Section: Energy Consumption and Exergy Efficiencysupporting
confidence: 90%
“…Exergy analysis becomes more crucial, especially for the industrial (large-scale) high temperature heating applications, and it can reveal whether or not and by how much it is possible to design more efficient thermal systems by reducing the sources of existing inefficiencies. Several researchers (Dincer and Sahin, 2004;Akpinar et al, 2005a,b;Corzo et al, 2008;Erbay and Icier, 2009) concluded that exergy analysis gave more reliable evaluation about the performance of thermal processing of food products rather than energy analysis. The minimization of the exergy losses, or equivalently the entropy generation, has a broader objective than the minimization of energy losses within a plant (Tekin and Bayramoglu, 1998).…”
Section: Introductionmentioning
confidence: 98%
“…Exergy is a measure of the potential of a stream to cause change, as a consequence of not being completely stable relative to the reference environment (Erbay and Icier, 2009). It is the measure of the availability of the energy in the system.…”
Section: Introductionmentioning
confidence: 99%